Sea buckthorn flavonoids and their derivatives: potential natural compounds for the treatment of diabetic cardiomyopathy - Zhang, Quan; Zhang, Jiahong; Ouyang, Yujie; Liu, Hongyan; Xie, Chunguang; Fu, Xiaoxu (Frontiers in Pharmacology, 2025)
Diabetic cardiomyopathy (DCM) is one of the most common complications of diabetes, characterized by high morbidity and disability rates, and can lead to heart failure. However, specific therapeutic agents for DCM are currently lacking. Natural compounds derived from traditional Chinese medicine have demonstrated potential in alleviating DCM through multiple mechanisms. Sea buckthorn flavonoids and their derivatives represent a promising class of natural compounds for the treatment of DCM. These compounds have been shown to improve DCM by combating oxidative stress, inhibiting inflammatory responses, regulating epigenetic modifications, modulating autophagy and apoptosis, maintaining mitochondrial homeostasis, alleviating endoplasmic reticulum stress, reducing advanced glycation end products (AGEs) level, and ameliorating cardiomyocyte hypertrophy and myocardial fibrosis. This article provides a brief overview of the pharmacological effects of sea buckthorn flavonoids and their derivatives and systematically reviews their mechanisms in improving DCM. The aim is to promote the effective utilization of herbal medicine and provide insights and references for the development of novel therapeutics for DCM.